Vaccines against Covid-19: Comparison, Limitations, the Decrease of Pandemic and the Perspective of Viral Respiratory - E. P. Kharchenko (Эпидемиология и вакцинопрофилактика)
Relevance. Vaccines are regarded as an effective means for control of the Covid-19 pandemic spreading and their search, analysis, and comparison of their features are important for elucidating the most safe and effective one. Aim. At the end of 2020 two types of vaccines (viral based vaccines and mRNA vaccines) have been licensed to vaccinate. The aim is to compare their features for objective substantiation of their application. Conclusions. As both vaccine types have high effectiveness in inducing antibodies to SARS-Cov-2 (in more 90% recipients) the utility of each vaccine type in blocking the Covid-19 pandemic spreading is beyond doubt. In both vaccine types eventually S protein is the antigen source, and they have limitations for vaccination. In comparison with the vector vaccines mRNA vaccines may induce serious complications, have the least potential to induce trained immunity and can be included into the recipient’s genome. The low frequency of influenza cases in the current epidemic season serves as an of interference between SARS-Cov-2 and influenza viruses. In epidemic seasons after the Covid-19 pandemic coronaviruses may dominate amongst viruses inducing acute respiratory viruses diseases. It is likely that the decline of the Covid-19 case count (in December-January) in Russia is determined by the heterologous collective immunity formed earlier.